2009
DOI: 10.1016/j.jbankfin.2008.09.021
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of household risky asset holdings: Australian evidence on background risk and other factors

Abstract: a b s t r a c tWe study the portfolio allocation decisions of Australian households using the relatively new Household, Income and Labour Dynamics in Australia (HILDA) Survey. We focus on household allocations to risky financial assets. Our empirical analysis considers a range of hypothesised determinants of these allocations. We find background risk factors posed by labor income uncertainty and health risk are important. Credit constraints and observed risk preferences play the expected role. A positive age g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
150
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(181 citation statements)
references
References 20 publications
12
150
5
Order By: Relevance
“…This positive association is in accordance with prior research (e.g., Hariharan et al 2000;Cardak & Wilkins 2009) and was also confirmed in the sensitivity analysis. Furthermore, risk tolerance was found to intervene in the relationship between financial literacy and decision-making, suggesting that less financially literate clients who tend to be less risk tolerant are more likely to allocate their funds into less risky assets.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This positive association is in accordance with prior research (e.g., Hariharan et al 2000;Cardak & Wilkins 2009) and was also confirmed in the sensitivity analysis. Furthermore, risk tolerance was found to intervene in the relationship between financial literacy and decision-making, suggesting that less financially literate clients who tend to be less risk tolerant are more likely to allocate their funds into less risky assets.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, it has been reported that risk tolerant individuals tend to invest less in risk free assets (Hariharan et al 2000) or risk averse households are more likely to have a lower proportion of their assets allocated in risky assets (Cardak & Wilkins 2009). Consistent with these studies, it is logical to expect (H7) that risk tolerant clients tend to invest in riskier products compared to less risk tolerant ones.…”
Section: Financial Risk Tolerance and Investment Decision-making (H7)mentioning
confidence: 74%
See 2 more Smart Citations
“…Subsequent empirical studies that have used panel methods to control for unobserved heterogeneity find either no direct effect or a small direct effect of health status on portfolio choices (see for example, Gupta, 2007;Coile and Milligan, 2009;Fan and Zhao, 2009;Love and Smith, 2010). Cardak and Wilkins (2009) find that the relationship between poor health status and risky asset holding becomes insignificant once risk and time preference variables are controlled for, using the Household Income and Labour Dynamics in Australia (HILDA) Survey. The authors argue that Australia's protective universal health care system might well play a role in explaining the absence of a direct effect, but do not take this element explicitly into account in their empirical analyses.…”
Section: Introductionmentioning
confidence: 99%